2018
DOI: 10.1111/scd.12335
|View full text |Cite
|
Sign up to set email alerts
|

Effects of general anesthesia on postoperative sleep cycles in dentally disabled patients

Abstract: Aims:Although it has been reported that general anesthesia affect the perioperative sleep cycle, no studies have yet evaluated how general anesthesia affects dentally disabled patients. In this study, we investigated the alteration of perioperative sleep cycles in dentally disabled patients receiving dental treatment under general anesthesia. Subjects and methods:The study included 16 patients receiving dental procedures under general anesthesia. Using a sleep monitoring mat, the patients' sleep cycles were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…30 Most recently, we have reported that there was a significant disturbance of sleep cycle after general anesthesia in a disability patient who underwent dental treatment, due to possible severe agitation after anesthesia. 31 Therefore, we should carefully manage the behavioral condition of these pediatric patients during perioperative periods estimated with useful score.…”
Section: Clinical Implicationmentioning
confidence: 99%
“…30 Most recently, we have reported that there was a significant disturbance of sleep cycle after general anesthesia in a disability patient who underwent dental treatment, due to possible severe agitation after anesthesia. 31 Therefore, we should carefully manage the behavioral condition of these pediatric patients during perioperative periods estimated with useful score.…”
Section: Clinical Implicationmentioning
confidence: 99%
“…Respiratory failure is one of the serious complications after general anesthesia, and its incidence is as high as 3% [ 4 ]. Respiratory failure is the dysfunction of pulmonary ventilation and ventilation caused by various reasons, which can lead to an inability to carry out effective gas exchange, leading to hypoxia with carbon dioxide retention, which leads to a series of clinical synthesis of physiological and metabolic disorders [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…General anesthesia is a state of hyporesponsiveness induced medically that resembles natural sleep. Studies have shown that general anesthesia can lead to decreases in rapid eye movement (REM) and slow-wave sleep (SWS), resulting in postoperative sleep disturbance [5,6]. Previous studies have also found that age, preoperative comorbidities, and severe surgical stimulation are independent risk factors associated with postoperative sleep disorders [7,8].…”
Section: Introductionmentioning
confidence: 99%